The Role of Formal and Informal Institutions in Shaping the Challenges Faced by Social Entrepreneurs: A Cross-Country Analysis Between Egypt and Tunisia - Magdy Saleh, Mirna (AUC Knowledge Fountain, 2026)
This study explores how formal and informal institutional contexts influence social entrepreneurs in Egypt and Tunisia; Tunisia is characterized by legal recognition and a framework governing social enterprises, whereas Egypt does not have a legal framework. Both countries are characterized by prolonged political uncertainty and high levels of informality. Utilizing Institutional theory as the main conceptual framework, the study explores how different contextual factors shape the challenges and opportunities faced by social entrepreneurs. Drawing on qualitative data from founders of social enterprises and experts in the field from both countries, this research aims to identify how institutional regulatory voids, normative pressures, and cognitive framings intersect to shape entrepreneurial challenges and opportunities. Both Egypt and Tunisia present a unique context for comparison due to their entrenched inequalities and hybrid formal-informal institutions. The findings of this study highlight that social entrepreneurs in Egypt and Tunisia operate within different but comparably constraining formal and informal institutions. Regarding the formal institutions, social entrepreneurs in Egypt mainly face issues related to bureaucratic system, weak rule of law, and donor influence. Tunisian social entrepreneurs suffer from regulatory failure and ineffective implementation of the new law on social enterprises. For informal institutions, social entrepreneurs in Egypt have been suffering from limited and ineffective social entrepreneurship education, as well as restrictive informal market agreements and gendered social expectations. Whereas in Tunisia, the informal institutions have been substituting the formal institutions through the reliance on informal networks for enterprise growth as well as reliance on entrepreneurial knowledge. This study 8 addresses a gap in the literature through providing insights in the MENA region as well as shedding light on how formal and informal institutions interact, from a multidimensional perspective. Finally, the study provides insights for policymakers and international development agencies aiming to foster and encourage entrepreneurship as a tool for tackling social issues. This contribution is highly relevant in post-crisis recovery countries, where institutional instability persists.